2020
DOI: 10.1016/j.compfluid.2019.104389
|View full text |Cite
|
Sign up to set email alerts
|

Triple decomposition of velocity gradient tensor in homogeneous isotropic turbulence

Abstract: The triple decomposition of a velocity gradient tensor is studied with direct numerical simulations of homogeneous isotropic turbulence, where the velocity gradient tensor ∇u is decomposed into three components representing an irrotational straining motion (∇u) EL , a rigid-body rotation (∇u) RR , and a shearing motion (∇u) SH . Strength of these motions can be quantified with the decomposed components. A procedure of the triple decomposition is proposed for three-dimensional flows, where the decomposition is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 27 publications
6
40
0
Order By: Relevance
“…These distributions of , and in the planar jet are consistent with DNS results of homogeneous isotropic turbulence (Nagata et al. 2020).
Figure 7.Colour contour plots of ( a ) , ( b ) and ( c ) on an plane in the planar jet with ().
…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These distributions of , and in the planar jet are consistent with DNS results of homogeneous isotropic turbulence (Nagata et al. 2020).
Figure 7.Colour contour plots of ( a ) , ( b ) and ( c ) on an plane in the planar jet with ().
…”
Section: Resultssupporting
confidence: 89%
“…2015; Nagata et al. 2020). The shear layers in the planar jet are investigated with the method proposed in Watanabe et al.…”
Section: Shear Layer Analysis Based On the Triple Decomposition Of The Velocity Gradient Tensormentioning
confidence: 99%
See 1 more Smart Citation
“…This decomposition has led to important insight into small-scale intermittency [1][2][3], intense structures in turbulence [4][5][6][7] and local streamline geometry [8][9][10]. However, recent studies [11][12][13] have shown that strain-rate and vorticity do not clearly identify the presence of normal-straining and rigid-body-rotation of the fluid. The presence of shear in both strain-rate and vorticity often obscures our understanding of some of the fundamental phenomena in turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been used for vortex-structure identification and investigation of internal shear layers in wall-bounded flows [14][15][16]. It has recently been used for investigating regions of strong shearing or rotation and detecting internal shear layer in homogeneous isotropic turbulence at Taylor Reynolds numbers, Re λ = 27 and 140 [13]. Aside from Kolář's method, Gao and Liu [12] formulated a "Rortex"-based VGT decomposition for locally fluid-rotational points (VGT has complex eigenvalues) in a turbulent flow field.…”
Section: Introductionmentioning
confidence: 99%